INTEGRASI GENDER DALAM PENGUATAN EKONOMI MASYARAKAT PESISIR - NUR SUHAETI, RITA; BASUNO, EDI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006)
To implement gender mainstreaming activity in relation to regional development, mainly for coastal development, a study on gender mainstreaming had been carried in two districts, namely Buton in Southeast Sulawesi and Cirebon in West Java out from June to December 2003. Data and information were collected using Focused Group Discussion approach as well as village level profiles and monograph. Gender analysis using Harvard Framework was implemented, covering profiles of participation, access, control and influencing factors. The study results showed that in Buton, labor division between man and woman in sea weed farming was relatively balanced. Participation rate of the household members, both in domestic, public and social sector in both studied locations was relatively similar. The role of Women Empowerment Division of The Agency for Society Empowerment (ASE) in Cirebon has not been optimal and still learning to find out suitable activities to meet its mandates. In Buton District, there was a coordination problem in implementing gender mainstreaming program, because there were two institutions both claimed responsible in implementing gender mainstreaming program. One important thing that has never been conducted in the two districts was to create collaboration among institutions responsible for the gender mainstreaming implementation. In the future, The District Level Marine and Fishery Service Office should work in collaboration with the ASE and they have to discuss how to incorporate gender aspects in coastal development including in Economic Empowerment for Coastal Community.
Keywords: Gender Mainstreaming, Coastal Area, Fishery, Community Development